Low educational status correlates with a high incidence of mortality among hypertensive subjects from Northeast Rural China - Yu, Shasha; Guo, Xiaofan; Li, GuangXiao; Yang, Hongmei; Zheng, Liqiang; Sun, Yingxian (Frontiers in Public Health, 2022)
Objective: Cumulative evidence indicates that education plays a major role in predicting cardiovascular risk factors. In this study, we intend to examine the possible relationship between education status and mortality in a large general subject from rural China. Methods: Adult hypertensive subjects (n = 5,227, age = 57.22 ± 10.18 years; 49.1% men) were recruited from general population surveys (Northeast China Rural Cardiovascular Health Study). Their educational status was categorized into two groups as follows: (1) Low education (illiterate or lower than primary school) and (2) medium-high education (higher than primary school). Cardiometabolic comorbidities, related cardiovascular risk factors, and echocardiographic measurements were analyzed in both groups. Results: Less educated hypertensive subjects had significantly higher prevalence of obesity, diabetes, dyslipidemia, and left ventricular hypertrophy than medium-high educated hypertensive subjects. In the medium-high educated subjects, a significant increase in left ventricular ejection fraction and lower rate of antihypertensive medication was found. Cox proportional hazards analysis indicated that medium-high education was independently associated with all-cause mortality (hazard ratio = 0.76; 95% confidence interval, 0.58, 0.99; P = 0.043) and cardiovascular mortality (hazard ratio = 0.65; 95% confidence interval, 0.44, 0.96; P = 0.028). Conclusion: Education may act as the best predictor of all-cause and cardiovascular mortality in rural hypertensive subjects. This finding suggests that in rural areas, education is likely to represent a cardiovascular specific risk factor and should be evaluated in the strategies of hypertension.